12/15‐Lipoxygenase deficiency reduces densities of mesenchymal stem cells in the dermis of wounded and unwounded skin. (17th July 2014) - Hong, S.; Alapure, B.V.; Lu, Y.; Tian, H.; Wang, Q.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Mesenchymal stem cells (MSCs) are known to be recruited into wounded skin and to promote healing. 12/15‐Lipoxgenase (LOX) and its products are present in the skin. 12/15‐LOX deficiency suppresses wound healing. What does this study add? We have discovered for the first time that LOX deficiency reduces MSC densities in the dermis of wounded and unwounded skin.